EARLY EMBRYONIC DEATH ASSOCIATED CHANGES IN STEROID HORMONES, LEPTIN, IGF-1, NITRIC OXIDE, ZINC AND COPPER IN MARES - MOHAMMAD, ASHA; KANDIEL, MMM; ABOU-EL-ROOS, MEA; EL AZAB, AI; ABO EL-MAATY, AM (The Indian Journal of Animal Reproduction, 2022)
Mares exhibting early embryonic death (EED, n=8), non-pregnancy (NP, n=12) and pregnancy (P, n=10) underwent ultrasound examination and blood sampling until week 4 post-breeding to assess the changes in reproductive and metabolic hormones, nitric oxide (NO), copper and zinc. Progesterone increased (p
Keywords: Early embryonic death; IGF-1; Mare; Nitric oxide; Leptin